2022
DOI: 10.1101/2022.04.06.487301
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prediction of quality-control degradation signals in yeast proteins

Abstract: Effective proteome homeostasis is key to cellular and organismal survival, and cells therefore contain efficient quality control systems to monitor and remove potentially toxic misfolded proteins. Such general protein quality control to a large extent relies on the efficient and robust delivery of misfolded or unfolded proteins to the ubiquitin-proteasome system. This is achieved via recognition of so-called degradation motifs-degrons-that are assumed to become exposed as a result of protein misfolding. Despit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…We, therefore, opted to employ a machine-learning algorithm that we have established by using the PSI data to train a logistic regression model (Johansson et al, 2022). QCDPred provided each amino acid with a unique value, based on its predicted contribution to degron potency (Johansson et al, 2022). Consequently, protein stability maps were formed for all proteins comprising the tested library that attained 100% coverage (N = 306), each includes experimental PSI values for each peptide, average PSI values for each amino acid, and QCDPred probability scores ( Supplemental Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We, therefore, opted to employ a machine-learning algorithm that we have established by using the PSI data to train a logistic regression model (Johansson et al, 2022). QCDPred provided each amino acid with a unique value, based on its predicted contribution to degron potency (Johansson et al, 2022). Consequently, protein stability maps were formed for all proteins comprising the tested library that attained 100% coverage (N = 306), each includes experimental PSI values for each peptide, average PSI values for each amino acid, and QCDPred probability scores ( Supplemental Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…This implies that for most QCAP degrons to become active, the protein must be structurally perturbed so that the degron is exposed. Indeed, we have found that for disordered proteins and regions there is a correlation between the presence of predicted degrons and the abundance and half-lives of the proteins (Johansson et al, 2022). Altogether, our data indicate that QCAP degrons are enriched in bulky hydrophobic TMD-like entities.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations